Changes in Support Intervention Practices in Mathematics for 5-Year-Old Preschool Education: The Importance of a Collaborative and Reflective Process - Isabelle Deshaies (Education Sciences)
Preschool mathematics support remains insufficient, which can limit children’s skill development and impact their long-term academic success. This study explores how collaboration between researchers and teachers can enhance these practices. It is based on the Classroom Assessment Scoring System (CLASS) model, which examines three key dimensions: concept development, language modeling, and the quality of feedback. This theoretical framework highlights the importance of pedagogical interactions in supporting early mathematical learning. A mixed-methods, longitudinal approach was adopted. Over three years, six teachers participated in five collaborative sessions per year. Systematic CLASS observations, questionnaires, interviews, and reflective journals were used to assess the evolution of teaching practices. The results reveal a significant improvement in the quality of mathematics support, particularly in concept development. However, feedback and language modeling progressed more slowly. Integrating mathematics into spontaneous situations, such as free play, remains a challenge. The discussion emphasizes the importance of continuous pedagogical support to further strengthen these practices and promote more interactive and contextualized learning experiences.